Experimental and numerical study of a generic conventional submarine at 10° yaw. (1st April 2016) - Fureby, C.; Anderson, B.; Clarke, D.; Erm, L.; Henbest, S.; Giacobello, M.; Jones, D.; Nguyen, M.; Johansson, M.; Jones, M.; Kumar, C.; Lee, S.-K.; et al.
Abstract: This investigation discusses the flow physics of the fully appended DSTO generic submarine model at both straight ahead conditions and during a 10° side-slip. Reynolds Averaged Navier Stokes (RANS) and Large Eddy Simulation (LES) computations have been performed and are compared with model-scale experiments. The experiments have been carried out in the DSTO Low-Speed Wind Tunnel, with data collected using pressure probes, Particle Image Velocimetry (PIV) and flow visualization using wool-tuft streamers. Computational studies using LES on unstructured meshes of up to 340 million cells provide detailed surface and off-body flow field data, complementing the experimental investigations and providing the opportunity for reciprocal validation of experiments and computations. Surface-flow patterns for the DSTO generic submarine model at 10° yaw and a freestream Reynolds ( Re ) number, based on wind tunnel speed and hull length, of Re =4.5×10 6 were obtained. The cross-stream velocity for the DSTO generic submarine model at 10° yaw and Re =2.7×10 6 was measured using PIV. The in-plane velocity was measured at three streamwise locations corresponding to 65%, 84% and 98% of the submarine model length. LES computations were performed using an incompressible LES flow solver developed using OpenFOAM and unstructured tetrahedral grids generated utilizing a patch-based approach to facilitate high near-wall resolutions and arbitrary refinement for appendage wakes. Highlights: Experimental study of a generic submarine hull at both straight ahead and at 10° yaw. Computational (using both RANS and LES) study of a generic submarine hull at both straight ahead and at 10° yaw. Experimental data and RANS and LES results provide reciprocal validation. New information about the key flow physics at both straight ahead and at 10° yaw. Results have strong implications of hull design and maneuvering.